PERAN LITERASI DIGITAL DI ERA ARTIFICIAL INTELLEGENCE TERHADAP KUALITAS PEMBELAJARAN MAHASISWA: STUDI PUSTAKA: Analisis Konseptual dan Temuan Penelitian tentang Literasi Digital Mahasiswa dalam Pembelajaran Berbasis AI - Itsnaini, Wulida; Tzanisa, Khalisya; Madania, Ismi; Rihhadatul ‘Aisy, Rahmah; Ammar Yazid, Muhammad; Sulistyani, Anjar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The integration of Artificial Intelligence (AI) in higher education creates a new paradigm and challenges, making digital literacy a crucial foundation. This literature study was conducted to analyze the development of students' digital literacy in the AI era and examine its role in improving the quality of learning. The research method used is a systematic review of relevant literature, such as scientific journals and books. The review reveals that the development of students' digital literacy is dynamic, with technical skills generally being good, but critical aspects such as information evaluation, digital ethics, and resilience to misinformation still need improvement. Regarding its role, digital literacy proves to be a determining factor in utilizing AI (such as ChatGPT and Quillionz) optimally, critically, and ethically. This role includes personalizing learning, collaboration, and plagiarism prevention. It is concluded that improving the quality of learning in the AI era highly depends on strengthening comprehensive digital literacy, which includes not only technical competencies but also cognitive and ethical competencies. Therefore, digital literacy is no longer just a supplement, but a core necessity to shape independent and responsible learners in a complex digital ecosystem.